Effectiveness of family involvement in newly diagnosed type 2 diabetes patients: a follow-up study. Issue 5 (May 2016) - Shi, Mai; Xu, Mei-Yan; Liu, Zhao-Lan; Duan, Xue-Ying; Zhu, Yan-Bo; Shi, Hui-Mei; Jiang, Bo; Zhang, Xiao-Mei; Yu, Xiao-Han
Highlights: Family-involved education is beneficial to glucose control. Family-involved education is beneficial to increasing the KAP scores. Family-involved education is beneficial to increasing the HRQoL of patients. Family-involved education is beneficial to body weight control. Health education should encourage the family to participate the whole process to improve the efficacy. Abstract: Objective: To investigate the effects of family-involvement on health education for T2DM from the aspects of knowledge, attitude and practice (KAP), health-related quality of life (HRQoL), body mass index (BMI) and glucose control. Methods: A follow-up study was performed and patients with newly diagnosed T2DM were divided into family-involved group (FIG, n = 60) and single-involved group (SIG, n = 60). Hierarchical linear models were used to assess within-group changes and between-group differences in the glycosylated hemoglobin A1c (HbA1c), KAP, SF-36 and BMI. Results: Significant improvements in FIG along with significant differences between-group were seen for HbA1c levels (9.73, 8.92, 5.55, 5.79, 5.30 vs. 10.05, 9.53, 6.36, 8.41, 6.58) in baseline, M3, M6, M12, M24 compared with SIG, respectively (all P ≤ 0.001). Significant improvements in FIG along with significant differences between-group were seen for KAP (16.23, 46.98, 48.93 vs. 16.65, 29.07, 37.62), SF-36 (78.04, 92.68, 92.34 vs. 74.96, 77.03, 78.25), and BMI (24.74, 23.46, 22.96 vs. 24.00, 23.45, 23.50) in baseline, M12 and M24, respectively (all P ≤ 0.05). Conclusion: Family involvement is beneficial to the control of T2DM and should be suggested for T2DM newly diagnosed. Practice implications: Health education should encourage the family to participate in the whole process to improve the efficacy of education.